(3GdYbhO GddDdDjI aj JGQjN GdOhdI GdQShdjIs - (3GdNRQLj , ehab GdOjf CHh GdMSf,J (B812 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3hai SfI EMOi hKdGKjf LgR GdSdWGf fhQ GdOjf NRGfI YXjeI Edi GdTQja QGLM Hf bJGOI s
(3BNQgG (B:s
(3BNQ GdehLhO efg hcGf eVehf GdQSGdI JbQjQ GdMGd hCf GdSdWGf bO QLY YeG cGf bO YRe Ydjg hai gPg GdSfI Jhai Gdabjg GHf Ydi Hf eMeO Hf CHj HcQ s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdeNWhWI Hbde bdjd GdfbW hHgG bdjd ef GdJQbjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B150 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs